Overview of Applications for the Development of Logical Thinking of Children of Primary School Age - Haman, Ivan (Educological discourse, 2023)
The article sheds light on the problem of developing logical thinking of primary school students through the use of digital technologies, namely, mobile applications. A general overview of popular mobile applications that contribute to the productive development of logical thinking of elementary school students is conducted. It is analyzed how exactly mobile applications affect the educational activity of students, as well as what place mobile applications occupy at the current stage of information technology development. The degree of popularity of mobile applications and the level of their development are considered. It is analyzed how mobile learning (M-learning) affects the development of students' cognitive activity. Advantages and disadvantages of mobile learning in education are considered and characterized. Some applications that can be used during training are presented. Analyzed mobile applications, with low technical requirements, which are a powerful tool for studying digital technologies that are used in the world and take education to a new level, providing productive learning of the necessary knowledge. The article highlights which mobile applications have the potential to influence the development of logical thinking. It was studied how applications allow children to solve logical problems, puzzles, games, which directly affect the development of critical and spatial thinking, train memory and attention, and develop motor skills. Considered how mobile applications expand the capabilities of the teacher and serve as an excellent tool for the development and improvement of students' skills.